Shakespeare reproduced : the text in history and ideology - Howard, Jean E. (Jean Elizabeth), 1948-; O'Connor, Marion F. (Routledge library editions - Shakespeare : history & politics., 2005)
First published in 1987. The essays in Shakespeare Reproduced offer a political critique of Shakespeare's writings and the uses to which those writings are put Some of the essays focus on Shakespeare in his own time and consider how his plays can be seen to reproduce or subvert the cultural orthodoxies and the power relations of the late Renaissance. Others examine the forces which have produced an overtly political criticism of Shakespeare and of his use in culture. Contributors include: Jean E Howard and Marion O'Connor, Walter Cohen, Don E Wayne, Thomas Car.